Efficacy of Botulinum Toxin for Treating Sialorrhea in Neuromuscular Conditions - Singh, Harsh; Nene, Yash; Mehta, Tejas R.; Govindarajan, Raghav (Frontiers in Neurology, 2020)
Background: Drooling related to bulbar weakness and dysfunction is a common concern in patients with neuromuscular disease. While there are numerous medications to manage sialorrhea, they are often limited by side effects and lack of efficacy. Botulinum toxin has shown to benefit ALS patients in a few studies, but there is scant data on the benefit in other neuromuscular conditions. Objective: To assess the effectiveness of Botulinum toxin in reducing sialorrhea in patients with various neuromuscular disease. Design/Methods: 25 patients (19M, 6F; 54.36 ± 17.09 yr) with documented neuromuscular illness and concern for drooling was followed for 6 weeks after Botulinum toxin injection. These patients had one of the following diagnoses: Duchenne muscular dystrophy (3), myotonic dystrophy (3), oculopharyngeal muscular dystrophy (1), inclusion body myositis (2), primary lateral sclerosis (1), amyotrophic lateral sclerosis (9), spinal muscular atrophy type 2 and 3 (2), spinal-bulbar muscular atrophy (2), and Becker’s muscular dystrophy (2). A subjective drooling scale (1: markedly worse, 5: markedly better) and drooling thickness score (0=normal, 100=thick) was calculated on these patients prior to the injection and 4 and 6 weeks after the injection. Botulinum toxin 20-30 units were injected into bilateral parotid gland (70% of the dose) and submandibular gland (30% of the dose). Results: The drooling thickness score at before the injection was 75.2 ± 10.46. At 4 and 6 weeks, average scores reduced to 47.2 ± 6.14 and 18.8 ± 5.26, respectively (p < 0.05). The average pre injection perception about drooling was 3.0 (p < 0.05). The average change in perception was +0.84 and +1.28 at 4 and 6 weeks, respectively (p < 0.05) implying significant improvement. There were no reported adverse effects. Conclusion: This study provides preliminary evidence for the use of botulinum toxin for refractory sialorrhea for a variety of neuromuscular conditions. Keywords: Sialorrhea, drooling, botulinum toxin, muscular dystrophy, amyotrophic lateral sclerosis, neuromuscular